Hot topics in interventional cardiology: Proceedings from the society for cardiovascular angiography and interventions 2020 think tank. Issue 6 (25th August 2020) - Naidu, Srihari S.; Coylewright, Megan; Hawkins, Beau M.; Meraj, Perwaiz; Morray, Brian H.; Devireddy, Chandan; Ing, Frank; Klein, Andrew J.; Seto, Arnold H.; Grines, Cindy L.; Henry, Timothy D.; Rao, Sunil V.; et al.
Abstract: The society for cardiovascular angiography and interventions (SCAI) think tank is a collaborative venture that brings together interventional cardiologists, administrative partners, and select members of the cardiovascular industry community for high‐level field‐wide discussions. The 2020 think tank was organized into four parallel sessions reflective of the field of interventional cardiology: (a) coronary intervention, (b) endovascular medicine, (c) structural heart disease, and (d) congenital heart disease (CHD). Each session was moderated by a senior content expert and co‐moderated by a member of SCAI's emerging leader mentorship program. This document presents the proceedings to the wider cardiovascular community in order to enhance participation in this discussion, create additional dialogue from a broader base, and thereby aid SCAI and the industry community in developing specific action items to move these areas forward.